The "Battle" of Managing Language Barriers in Health Care. (December 2016) - Steinberg, Emma M.; Valenzuela-Araujo, Doris; Zickafoose, Joseph S.; Kieffer, Edith; DeCamp, Lisa Ross
Providing safe and high-quality health care for children whose parents have limited English proficiency (LEP) remains challenging. Reports of parent perspectives on navigating language discordance in health care are limited. We analyzed portions of 48 interviews focused on language barriers from 2 qualitative interview studies of the pediatric health care experiences of LEP Latina mothers in 2 urban US cities. We found mothers experienced frustration with health care and reported suboptimal accommodation for language barriers. Six themes emerged relevant to health care across settings: the "battle" of managing language barriers, preference for bilingual providers, negative bias toward interpreted encounters, "getting by" with limited language skills, fear of being a burden, and stigma and discrimination experienced by LEP families. Parents' insights highlight reasons why effective language accommodation in health care remains challenging. Partnering with families to address the management of language barriers is needed to improve health care quality and safety for LEP patients and families.